Effectiveness of strain and dopants on breaking the activity-stability trade-off of RuO2 acidic oxygen evolution electrocatalysts - Yang Liu; Yixuan Wang; Hao Li; Min Gyu Kim; Ziyang Duan; Kainat Talat; Jin Yong Lee; Mingbo Wu; Hyoyoung Lee (Nature Communications)
Abstract Ruthenium dioxide electrocatalysts for acidic oxygen evolution reaction suffer from mediocre activity and rather instability induced by high ruthenium-oxygen covalency. Here, the tensile strained strontium and tantalum codoped ruthenium dioxide nanocatalysts are synthesized via a molten salt-assisted quenching strategy. The tensile strained spacially elongates the ruthenium-oxygen bond and reduces covalency, thereby inhibiting the lattice oxygen participation and structural decomposition. The synergistic electronic modulations among strontium-tantalum-ruthenium groups both optimize deprotonation on oxygen sites and intermediates absorption on ruthenium sites, lowering the reaction energy barrier. Those result in a well-balanced activity-stability profile, confirmed by comprehensive experimental and theoretical analyses. Our strained electrode demonstrates an overpotential of 166 mV at 10 mA cm−2 in 0.5 M H2SO4 and an order of magnitude higher S-number, indicating comparable stability compared to bare catalyst. It exhibits negligible degradation rates within the long-term operation of single cell and PEM electrolyzer. This study elucidates the effectiveness of tensile strain and strategic doping in enhancing the activity and stability of ruthenium-based catalysts for acidic oxygen evolution reactions.